Penentuan Kombinasi Produk Roti Menggunakan Metode Linear Programming Model Simplex Untuk Memaksimalkan Keuntungan - Asep Warman; Lili Karmela Fitriani; Tatang Rois (FEB Universitas Sultan Ageng Tirtayasa, 2021)
IKM Z & J Cookies is a SMEs industry engaged in the food sector, manufacture of pastries and bread in Kuningan Regency, West Java. The problem in this research was difficulty in determine the effective and efficient production with the available resources and sufficient materials in order to obtain maximum benefits. Based on the results of the analysis that has been done, the bakery products using the company method produced 3,500 pcs while using the linear programming method of the simplex model 3,555 pcs, the difference in production was 55 pcs of bread if using the simplex model linear programming method. as well as the net profit when using the company method of Rp. 4,991,930, while using the simplex model linear programming method of Rp. 5,101,930 so that the difference in profit was Rp. 110,000 per production day, therefore determining the combination of production using the simplex model linear programming method had the maximum benefit.